An Economic Anatomy of Optimal Climate Policy - Juan Moreno-Cruz; Gernot Wagner; David W. Keith (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper introduces geoengineering into an optimal control model of climate change economics. Together with mitigation and adaptation, carbon and solar geoengineering span the universe of possible climate policies. Their wildly different characteristics have important implications for climate policy. We show in the context of our model that: (i) the optimal carbon tax equals the marginal cost of carbon geoengineering; (ii) the introduction of either form of geoengineering leads to higher emissions yet lower temperatures; (iii) in a world with above-optimal cumulative emissions, only a complete set of instruments can minimize climate damages.
Keywords: D90; O44; Q48; Q54; Q58; 330; climate change; climate policy; mitigation; adaptation; carbon geoengineering; carbon dioxide removal; solar geoengineering; solar radiation management